Stamp set commemorating 50th anniversary of Oklahoma statehood - United States Postal Service (1957)
Set of four postage stamps celebrating the 50th anniversary of Oklahoma's statehood. Depicts an atomic model with an arrow piercing its nucleus overlaying a silhouette of the state of Oklahoma. Reflects Oklahoma’s evolution from the frontier days before statehood to the new frontiers expressed by atomic energy during the 1950s.
Keywords: Postage stamps; Postmarks; Commemorative postage stamps; Oklahoma; Statehood (American politics); Nuclear energy; Science on postage stamps